2009
DOI: 10.1002/gps.2372
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol and tobacco consumption, and apolipoprotein E genotype, on the age of onset in Alzheimer's disease

Abstract: The results suggest that APOE epsilon4 and heavy drinking and heavy smoking lower the age of onset for AD in an additive fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 42 publications
2
69
2
3
Order By: Relevance
“…Individuals who are homozygous for the ApoE4 allele develop Alzheimer's disease earlier at a mean age of 70 years. Furthermore, individuals homozygous for the ApoE4 allele, as well as tobacco smokers and heavy alcohol consumers are more likely to be diagnosed with Alzheimer's disease approximately 10 years earlier than those with none of these three risk factors [139]. The ApoE4 allele is also a risk factor for hypercholesterolemia.…”
Section: Amyloid-β and Apoe-epsilon 4 Allelementioning
confidence: 99%
“…Individuals who are homozygous for the ApoE4 allele develop Alzheimer's disease earlier at a mean age of 70 years. Furthermore, individuals homozygous for the ApoE4 allele, as well as tobacco smokers and heavy alcohol consumers are more likely to be diagnosed with Alzheimer's disease approximately 10 years earlier than those with none of these three risk factors [139]. The ApoE4 allele is also a risk factor for hypercholesterolemia.…”
Section: Amyloid-β and Apoe-epsilon 4 Allelementioning
confidence: 99%
“…29 30 Moderate consumption of alcohol has been observed to be a protective factor in non-ApoE ε4 carriers, 31 32 whereas heavy drinking may lower the age of onset of Alzheimer's disease. 33 Caffeine consumption has been associated with a reduction in density of white matter lesions and possible delaying of onset of dementia, 34 and inadequate consumption of water has been observed to increase risk. 35 Nicotine intake has also been observed to decrease the risk of dementia, 36 although more recent studies have suggested that it may increase it and also bring forward age of onset with an ApoE ε4 interactive effect.…”
Section: Candidate Exposuresmentioning
confidence: 99%
“…It has been described in south Asian men a higher risk to develop CHD as compared to men from other genetic backgrounds [30,31]. Furthermore, cigarette smoking is positively correlated to CHD [1] and to Alzheimer's Disease [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…As positive correlations between cigarette smoking and Alzheimer's Disease have been identified [28,29], the aim of the present study was to investigate the plasma and erythrocyte membrane phospholipid fatty acid profiles of young adult males of Indian, Sri-Lankan or Bangladeshi genetic backgrounds with a smoking habit. The population recruited is relatively young and smokes between 20 and 60 cigarettes per week.…”
Section: Introductionmentioning
confidence: 99%